2019
DOI: 10.1111/trf.15461
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion‐related immune modulation: functional consequence of extracellular vesicles?

Abstract: Extracellular vesicles (EVs) are small, subcellular vesicles that are released from a variety of cells and play important roles in cell-to-cell communication.• Transfused blood products, including red blood cell, platelet, and plasma products contain EVs that are capable of interacting with and altering immune cell function.• The extent to which EVs may contribute to clinically meaningful immunomodulatory effects of transfusion remains unclear and deserving of further study.T he term extracellular vesicle (EV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…These results were in good agreement with a previous study showing that extracellular vesicles in RBCs could be separated using ultracentrifugation ( 4 ). RBCs contain EXs from various cell types, such as platelets and white blood cells ( 3 ). In this study, we did not identify the cell origin of EXs for two reasons as follows: (i) the valuable contents in EXs from different cells might be the same ( 8 ), and (ii) we focused on the pathogenic contents in the total EXs from RBCs rather than those in erythrocyte-derived EXs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were in good agreement with a previous study showing that extracellular vesicles in RBCs could be separated using ultracentrifugation ( 4 ). RBCs contain EXs from various cell types, such as platelets and white blood cells ( 3 ). In this study, we did not identify the cell origin of EXs for two reasons as follows: (i) the valuable contents in EXs from different cells might be the same ( 8 ), and (ii) we focused on the pathogenic contents in the total EXs from RBCs rather than those in erythrocyte-derived EXs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the potential immunologic effect of extracellular vesicles from RBCs has attracted growing interest ( 3 ). Extracellular vesicles are small double-membrane vesicles that can be secreted by RBCs and increase in number with storage time.…”
Section: Introductionmentioning
confidence: 99%
“…Transfusion of blood products may affect measurements of EVs because they are EV rich. 48 A total of nine patients (27%) received transfusion of blood products as part of in-hospital standard care during the blood sampling period, and some patients also received packed red blood cells as part of prehospital standard care. Some patients received anticoagulants, but this is unlikely to have influenced the results because the patient’s plasma was washed away before EV-associated procoagulant activity measurements.…”
Section: Discussionmentioning
confidence: 99%
“…However, in stored RBC supernatants, apart from leukocytes and the substances they release, EVs are also constantly secreted by RBCs in storage (77). EV numbers typically increase with longer storage durations and likely contribute to TRIM (77,78).…”
Section: Trim In Patients With Cancer Receiving Rbc Transfusionsmentioning
confidence: 99%
“…Previous studies have indicated that stored RBC-derived EVs are able to mediate TRIM and proinflammatory effects (78)(79)(80). RBC-derived EVs have been reported to inhibit the proliferation and activation of B cells and macrophages in a dose-dependent manner.…”
Section: Trim In Patients With Cancer Receiving Rbc Transfusionsmentioning
confidence: 99%